IMPLEMENTATION OF CAPITAL INVESTMENTS IN INTANGIBLE ASSETS: IMPLEMENTATION OF THE SOFTWARE - Левченко, Вікторія; Мірошник, Олексій (Socio-economic relations in the digital society, 2019)
In the article the system of automation of accounting for ensuring the effi ciency of capital investments is developed. Identifying the most appropriate soft ware for the enterprise is an important strategic decision. It can be based on the results of the survey of accounting offi cers and a number of expert experts to highlight the most important characteristics of accounting soft ware in the enterprise. The order of investing in intangible assets at the enterprise is determined. An analysis of each stage of its implementation, including analysis of soft ware requirements; conducting express survey; formation of a strategy of carrying out of works; creating a schedule; analysis and construction of the technical architecture and, as a result, the introduction of the soft ware into operation. Different interviewing methods are outlined in the company.According to the results of surveys and questionnaires consisting block diagram of material and information flows between the structural units. In the block diagram, a mechanism for selecting and preparing an enterprise technological system for the acquisition and introduction of soft ware is developed. Displays the accounting software considered depending on how it is received, according to which the software can be displayed as an object of fixed assets, intangible assets, lease or service charge. The computer system at the enterprise should have the appropriate level for the introduction of a new soft ware product. This system needs to be investigated, refined and updated if it does not meet the requirements.Th e final introduction of the soft ware into operation occurs after the adaptation and testing of the soft ware product. The completion of works is made by the protocol of introduction into industrial exploitation.At this stage, it is necessary to determine the order of the work, to develop a schedule for the transition of individual workers to work in the new system. Sometimes parallel accounting is allowed for some time, but it is desirable not more than one reporting period. In case of capital investment in intangible assets, after the introduction of this system, the risks associated with the discrepancy of soft ware capabilities with the needs of the enterprise will be minimized.